2017
DOI: 10.1073/pnas.1620519114
|View full text |Cite
|
Sign up to set email alerts
|

Cerberus–Nodal–Lefty–Pitx signaling cascade controls left right asymmetry in amphioxus

Abstract: Many bilaterally symmetrical animals develop genetically programmed left-right asymmetries. In vertebrates, this process is under the control of Nodal signaling, which is restricted to the left side by Nodal antagonists Cerberus and Lefty. Amphioxus, the earliest diverging chordate lineage, has profound left-right asymmetry as a larva. We show that Cerberus, Nodal, Lefty, and their target transcription factor Pitx are sequentially activated in amphioxus embryos. We then address their function by transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 38 publications
10
77
1
1
Order By: Relevance
“…Other techniques that have represented great advances are the induction of spawning by temperature change that I already mentioned above, which allows one to obtain embryos on a daily basis during the spawning season, or the development of husbandry techniques with artificial sea water, which allows laboratories inland to work with amphioxus. Obtaining the complete life cycle of amphioxus in captivity has also been a very important step, particularly to create knockout lines of amphioxus using transcription activator‐like effector nucleases, (TALEN)‐based knockout . This knockout technique allowed Li and collaborators to demonstrate the master role of the Nodal antagonist Cerberus in the control of left‐right asymmetries in amphioxus .…”
Section: From Comparative Anatomy To Functional Genomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other techniques that have represented great advances are the induction of spawning by temperature change that I already mentioned above, which allows one to obtain embryos on a daily basis during the spawning season, or the development of husbandry techniques with artificial sea water, which allows laboratories inland to work with amphioxus. Obtaining the complete life cycle of amphioxus in captivity has also been a very important step, particularly to create knockout lines of amphioxus using transcription activator‐like effector nucleases, (TALEN)‐based knockout . This knockout technique allowed Li and collaborators to demonstrate the master role of the Nodal antagonist Cerberus in the control of left‐right asymmetries in amphioxus .…”
Section: From Comparative Anatomy To Functional Genomicsmentioning
confidence: 99%
“…Obtaining the complete life cycle of amphioxus in captivity has also been a very important step, particularly to create knockout lines of amphioxus using transcription activator‐like effector nucleases, (TALEN)‐based knockout . This knockout technique allowed Li and collaborators to demonstrate the master role of the Nodal antagonist Cerberus in the control of left‐right asymmetries in amphioxus . Other techniques allowing functional studies developed by various laboratories include the use of morpholinos to knockdown gene expression or the overexpression of a given gene through microinjection of capped‐mRNA.…”
Section: From Comparative Anatomy To Functional Genomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, Lefty itself negatively regulates the Smad2/3-mediated signaling and the expression of Nodal (Bisgrove et al, 1999;Branford and Yost, 2002;Feldman et al, 2002). A recent study that used gene-specific knock-out experiments in amphioxus showed that Smad2/3-mediated signaling activates Nodal and Lefty, and that Lefty strongly represses Nodal expression during the late gastrula/neurula stage (Li et al, 2017), suggesting that this autoregulatory loop also occurs during the blastula/early gastrula stages in amphioxus embryos. These Nodal-Lefty regulatory interactions may represent a reaction-diffusion system that operates during the axis establishment in deuterostomes (Branford and Yost, 2002;Duboc et al, 2008).…”
Section: Nodal/vg1/activin Signaling Plays a Key Role In The Formatiomentioning
confidence: 99%
“…Understanding the evolution of genes that are involved in early developmental processes represents an important challenge in biology (Gilbert, ). In most of the cases, the information that is available is restricted to the presence of a particular developmental pathway, and of the genes that participate in it, but much less is known regarding the evolutionary history of the genes and pathways (Jones, Kuehn, Hogan, Smith, & Wright, ; Joseph & Melton, ; Lagadec et al, ; Levin, Johnson, Stern, Kuehn, & Tabin, ; Li et al, ; Raya, Carlos, & Belmonte, ; Seleiro, Connolly, & Cooke, ; Tadjuidje et al, ).…”
Section: Introductionmentioning
confidence: 99%